Science and Technology Transmission for Society: Training on Development of Learning Tools for Teachers to Train Students' Critical Thinking Skills - Saiful Prayogi; Ni Nyoman Sri Putu Verawati (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2022)
The Science and Technology Transmission for Society (STTS) activity is a community service activity that aims to improve the ability of Madrasah Aliyah teachers in developing learning tools (RPP) and teaching materials (textbooks and worksheets) to train students' critical thinking skills. Partners in this activity, namely the Madrasah Aliyah Negeri (MAN) Sengkol and Madrasah Aliyah (MA) NW Remajun teacher groups. Both schools are located in Central Lombok district, NTB. Members of the partner groups in both schools consisted of teachers of Mathematics and Natural Sciences (Physics and Chemistry). This STTS activity has been carried out with a series of In Service Training (IST), On Service Training (OST) activities, as well as the implementation and measurement of students' critical thinking skills. IST activities provide education and training to the two partners on learning analysis, the concept of learning tools which include lesson plans and teaching materials (textbooks and worksheets), the concept of developing learning tools that can train students' critical thinking skills, and critical thinking ability test instruments. OST activities are carried out by providing assistance to the two partner groups in preparing lesson plans and teaching materials (textbooks and worksheets) that can train students' critical thinking skills, as well as preparing critical thinking ability test instruments. Implementation is carried out to ensure that the learning tools developed can train students' critical thinking skills. Furthermore, the measurement of students' critical thinking skills was carried out using the critical thinking skills test instrument that was developed previously. The results of STTS activities in general are that teachers in partner schools have the competence to develop learning tools to train students' critical thinking skills.